Divided we stand: reasons for and against strike participation in Amazon's German distribution centres. (1st April 2019) - Apicella, Sabrina; Hildebrandt, Helmut
Abstract : Little attention has been devoted to the individual motivations behind strike participation - particularly in minority strikes, such as the labour struggle affecting Amazon's German distribution centres. This study surveyed 223 Amazon employees asking questions relating to strike participation, income, reliance on trade unions, work dissatisfaction, employment status, professional background and demographic background. Our results, based on logistic regression analysis, evidenced that work dissatisfaction, reliance on trade unions, and having temporary or permanent positions predicted decisions vis-à-vis strike participation with 92% accuracy. The union's main goal, improving workers' income, did not play a major role.